1990
DOI: 10.1128/aem.56.6.1851-1857.1990
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rates of Digestion of Bacteria by Freshwater and Marine Phagotrophic Protozoa

Abstract: Differential decreases over time of two bacterial species, Escherichia coli and Enterococcus faecalis, in a freshwater and a marine ecosystem were observed and explained by a differential rate of digestion of these bacteria by phagotrophic flagellates and ciliates. For this purpose, fluorescence-labeled bacteria (FLB) were used and prepared from the two species cited above. The number of FLB was observed for 5 days in fresh and marine waters in the presence or absence (0.2-,unm-pore-size-filtered water) of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 39 publications
3
68
1
2
Order By: Relevance
“…The type of food bacterium also promoted different responses in the freshwater clone SRBM. This is consistent with reports for other protozoa [35,43]. The growth rate of SRBM was almost 1.5 times higher when fed with V. natriegens than with E. aerogenes although net stationary phase population was reduced by half.…”
Section: Inter-and Intra-specific Variationsupporting
confidence: 92%
“…The type of food bacterium also promoted different responses in the freshwater clone SRBM. This is consistent with reports for other protozoa [35,43]. The growth rate of SRBM was almost 1.5 times higher when fed with V. natriegens than with E. aerogenes although net stationary phase population was reduced by half.…”
Section: Inter-and Intra-specific Variationsupporting
confidence: 92%
“…Bitton et al (1983) found that E. coli and f2 coliphage in groundwater declined at rates of 0Á0066 and 0Á059 h À1 respectively. Other researchers have suggested that observed decreases in the concentrations of bacteria in freshwater may be a result of inhibitory substances (Klein and Alexander 1986), the activities of predatory and lytic organisms, temperature effects, aggregation, adsorption, sedimentation and sunlight induced damage (Flint 1987;Gonzalez et al 1990;Characklis et al 2005;Bertrand et al 2012;Pinon and Vialette 2018). Yet other researchers attribute observed increases in microbial concentrations to disaggregation, growth or 'regrowth' and resuscitation, the so-called bottle effect and repair of UV induced damage (Hortnagl et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria targeted by Entero1 experienced an earlier onset of decay, but slower decay, than targeted Bacteroides. Protozoan predators have been shown to prefer prey based on prey outer membrane characteristics (Gonzalez et al, 1990;Tarao et al, 2009), size (Simek and Chrzanowski, 1992), morphology (Justice et al, 2008) and perhaps growth rate (Pernthaler, 2005). Gram-positive Actinobacteria are notably resistant to grazing (Pernthaler et al, 2001) due to surface layer characteristics (Tarao et al, 2009).…”
Section: Decay Profiles Differ By Bacterial Target Groupmentioning
confidence: 99%